Classic reviews in tourism - Cooper Chris (New Delhi Viva Books, 2006)
Drawing together some of the leading authors in tourism, this text provides state-of-the-art reviews of research in fields of tourism. The text also revisits classic reviews which first appeared in Progress in Tourism, Recreation and Hospitality Manage
Keywords: Tourism